2020
DOI: 10.1038/s41467-020-19089-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and managing new risks on the Nile with the Grand Ethiopian Renaissance Dam

Abstract: When construction of the Grand Ethiopian Renaissance Dam (GERD) is completed, the Nile will have two of the world’s largest dams—the High Aswan Dam (HAD) and the GERD—in two different countries (Egypt and Ethiopia). There is not yet agreement on how these dams will operate to manage scarce water resources. We elucidate the potential risks and opportunities to Egypt, Sudan and Ethiopia by simulating the filling period of the reservoir; a new normal period after the reservoir fills; and a severe multi-year droug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 56 publications
1
62
0
1
Order By: Relevance
“…There are numerous studies, which suggest that there is a lack of planning for the filling process of the GERD reservoir, especially the consideration of the negative future implications to Egypt and Sudan [9][10][11]. However, currently, there have been no studies that involve the monitoring of the filling process using satellite remote sensing datasets.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies, which suggest that there is a lack of planning for the filling process of the GERD reservoir, especially the consideration of the negative future implications to Egypt and Sudan [9][10][11]. However, currently, there have been no studies that involve the monitoring of the filling process using satellite remote sensing datasets.…”
Section: Introductionmentioning
confidence: 99%
“…17 , 34 , 35 ). An accounting of Sudan’s historical use of the Nile water is beyond the scope of this Egypt centric study but is reported to be 13–16.7 km 3 /year 18 , 19 , 21 . Much of the increased water demand in Egypt has been met by virtual water imports, which reached 40 km 3 in the 2010’s (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In the modern record, flows recorded at Aswan and Dongola have been slightly decreasing, as a result of increased withdrawal of natural flows upstream from Sudan's withdrawal of 4 km 3 in 1959 to current withdrawals of 13-16.7 km 3 (refs. [16][17][18][19][20][21].…”
Section: "Tmentioning
confidence: 99%
“…Moreover, the operation of the GERD would reduce Egypt's hydropower generation (Wheeler et al, 2016). Depending on how the GERD is operated during multi-year droughts, the dam could result in irrigation water deficits in Egypt (Wheeler, Jeuland, Hall, Zagona, & Whittington, 2020). Negotiations between Ethiopia, Sudan, and Egypt on the initial filling and long-term operation of the dam are ongoing since 2011.…”
mentioning
confidence: 99%
“…Several previous studies assessed the impacts of the GERD on Ethiopia, Sudan, and Egypt as a result of changes to water availability for irrigation and hydropower generation (Arjoon, Mohamed, Goor, & Tilmant, 2014;Basheer et al, 2020Digna et al, 2018a;Digna et al, 2018b;Eldardiry & Hossain, 2020;Elsayed, Djordjevic, Savic, Tsoukalas, & Makropoulos, 2020;Kahsay et al, 2019;King & Block, 2014;Liersch, Koch, & Hattermann, 2017;Mulat & Moges, 2014;Siddig, Basheer, & Luckmann, 2021;Wheeler et al, 2016Wheeler et al, , 2020Wheeler et al, 2018a , & Block, 2016). However, no study in the published literature analyzed the long-term impacts of the GERD on the riverine flood hazard along the Blue Nile and the Main Nile.…”
mentioning
confidence: 99%